2018
DOI: 10.1007/s12035-018-1331-2
|View full text |Cite
|
Sign up to set email alerts
|

Citalopram Reduces Aggregation of ATXN3 in a YAC Transgenic Mouse Model of Machado-Joseph Disease

Abstract: Machado-Joseph disease, also known as spinocerebellar ataxia type 3, is a fatal polyglutamine disease with no disease-modifying treatment. The selective serotonin reuptake inhibitor citalopram was shown in nematode and mouse models to be a compelling repurposing candidate for Machado-Joseph disease therapeutics. We sought to confirm the efficacy of citalopram to decrease ATXN3 aggregation in an unrelated mouse model of Machado-Joseph disease. Four-week-old YACMJD84.2 mice and non-transgenic littermates were gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
(76 reference statements)
0
22
0
Order By: Relevance
“…If a similar mechanism is occurring in vertebrates, this would be consistent with an aggregation preventive rather than disruptive mechanism, which is in accordance with our data. Importantly, pre-symptomatic treatment of a second MJD transgenic mouse model (YACMJDQ84.2) [35] with citalopram also resulted in a reduction in ATXN3 inclusions and abundance, and in the modulation of certain components of cellular proteostasis, including restoration of Hsp90beta levels in brains of mice treated with this drug [21]. The differential impact of citalopram treatment on ATXN3 proteotoxicity in the cerebellum, brainstem, and spinal cord seen in this work and in the study by Ashraf et al may reflect the distinct expression pattern/activation of 5-HT receptors [36][37][38]; therefore, it would be important to identify the specific 5-HT receptors required for citalopram's effect on toxicity and aggregation of mutant ATXN3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a similar mechanism is occurring in vertebrates, this would be consistent with an aggregation preventive rather than disruptive mechanism, which is in accordance with our data. Importantly, pre-symptomatic treatment of a second MJD transgenic mouse model (YACMJDQ84.2) [35] with citalopram also resulted in a reduction in ATXN3 inclusions and abundance, and in the modulation of certain components of cellular proteostasis, including restoration of Hsp90beta levels in brains of mice treated with this drug [21]. The differential impact of citalopram treatment on ATXN3 proteotoxicity in the cerebellum, brainstem, and spinal cord seen in this work and in the study by Ashraf et al may reflect the distinct expression pattern/activation of 5-HT receptors [36][37][38]; therefore, it would be important to identify the specific 5-HT receptors required for citalopram's effect on toxicity and aggregation of mutant ATXN3.…”
Section: Discussionmentioning
confidence: 99%
“…As the disease progresses, however, the ability of citalopram to prevent aggregation and neuronal loss may not be sufficient to cope with the already installed neurodegenerative process; hence, an early initiation of treatment may be required. Importantly, the safety profile of SSRIs [31] allows preventive treatment of mutation carriers as well as its administration after symptom installation, with treatment efficacy being reported in two rodent models of MJD [20,21]. Our previous results showed that presymptomatic citalopram treatment [20] exerted its effects mostly in the CNS-related symptoms rather than on the periphery (e.g., muscular strength).…”
Section: Discussionmentioning
confidence: 99%
“…We should give them a professional psychological assessment, as well as some psychological intervention and medication. At present, many experimental studies have shown that selective serotonin reuptake inhibitors (SSRIs) can reduce the neurotoxicity of SCA3 animal models [28,29], but whether the drug is effective in clinical trials and whether antidepressants can be used as a routine treatment for SCA still requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no disease-modifying therapies for SCA3. Reducing levels of mutant ATXN3 transcript or encoded protein, however, has effectively mitigated disease phenotypes in preclinical trials in SCA3 transgenic mouse models [1019, 36]. Accordingly, therapeutic approaches that deplete pathogenic ATXN3 proteins in the SCA3 brain appear promising.…”
Section: Discussionmentioning
confidence: 99%